1999
DOI: 10.1034/j.1399-3003.1999.14a30.x
|View full text |Cite
|
Sign up to set email alerts
|

An independent association between obstructive sleep apnoea and coronary artery disease

Abstract: Previous studies of sleep and breathing suggest an independent association between coronary artery disease (CAD) and obstructive sleep apnoea (OSA) in middle-aged males and females. These studies, however, were criticized because they did not properly adjust for all important confounding factors. In order to better control for the impact of these confounders, a case-control study was performed, matching for age, sex and body mass index (BMI), and additionally adjusting for hypertension, hypercholesterolemia, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
188
1
21

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(214 citation statements)
references
References 24 publications
3
188
1
21
Order By: Relevance
“…The study also confirmed that established cardiovascular diseases, such as coronary artery disease and congestive heart failure, are accompanied by a high prevalence of OSA. 19,20 Furthermore, the prevalence of OSA in patients with AF was substantially greater than the prevalence of OSA in patients with established cardiovascular disease but without past or current AF.…”
Section: Discussionmentioning
confidence: 99%
“…The study also confirmed that established cardiovascular diseases, such as coronary artery disease and congestive heart failure, are accompanied by a high prevalence of OSA. 19,20 Furthermore, the prevalence of OSA in patients with AF was substantially greater than the prevalence of OSA in patients with established cardiovascular disease but without past or current AF.…”
Section: Discussionmentioning
confidence: 99%
“…OSA may trigger the rupture of vulnerable plaques, leading to acute myocardial infarction 11,12 . OSA has been identified as an independent predictor of angiographic and clinical outcomes in coronary artery disease, such as cardiac death, myocardial infarction and reinfarction or revascularization after percutaneous coronary intervention 13,14 .…”
mentioning
confidence: 99%
“…2 Because sleep-disordered breathing (SDB) is associated with a number of cardiovascular diseases, 3 including hypertension, 4 heart failure, 5,6 and coronary artery disease, 7 it may be frequent in patients with implanted pacemakers or intracardiac defibrillators. However, many patients with SDB remain undiagnosed.…”
mentioning
confidence: 99%